Overview of Electrical Energy Planning in West Sumatera - Aditio Pribadi, Rizki; Syafii, Syafii (Andalasian International Journal of Applied Science, Engineering and Technology, 2021)
Electrical energy is one of the most important components in the development of an area. The development of sustainable development accompanied by rapid technological advances and an increase in living standards can cause the consumption of electrical energy to continue to increase, including in West Sumatra Province. To meet the needs of electrical energy in the future, it is necessary to build and develop the existing electrical system at PT. PLN (Persero) in order to serve the needs of electrical energy in the future. One of them is by predicting or predicting the demand for electrical energy in the next few years by utilizing historical data on the consumption of electrical energy in the past. In this study, the authors predict the electricity needs of West Sumatra Province from 2019 to 2028. The need for electrical energy tends to increase from year to year. In 2019 the need for electrical energy is 3,705 GWh, while in 2028 it is 6,980 GWh with an average growth in energy sales of 7.29 percent. The household sector has the highest demand for electrical energy in 2028, namely 3,769 GWh with an average percentage increase per year of 6.6 percent. Keywords: Power system planning, Electrical energy consumption, Generation planning and Electrification ratio.